Sosialisasi Pemberian Jahe Madu Untuk Mengurangi Ispa Pada Anak Di Wilayah RT. 04 Kelurahan Ponorogo Kec. Lubuklinggau Utara 2 - Wulan Dari; Eka Susi Widyawati; Dwi Cahya Novita Sari; Sintia Ana Dwita; Sella Rindian; Danur Azissah (Jurnal Pakar Pengabdian Kesehatan, 2025)
Acute Respiratory Infection (ARI) remains one of the most common health problems affecting children, particularly those of preschool age. Proper early management is essential to reduce symptoms and prevent further complications. Ginger and honey are natural ingredients known for their anti-inflammatory, antibacterial, and immune-boosting properties, making them suitable alternatives for alleviating ARI symptoms. This socialization activity aimed to improve mothers’ knowledge regarding the benefits of ginger-honey preparations and their application in managing mild ARI in children. The program was conducted in RT 04, Ponorogo Village, Lubuklinggau Utara II District, and was attended by 15 participants. An evaluation was carried out on a three-year-old child named Nadira Al-Maida who experienced ARI symptoms. The results showed that after receiving ginger-honey treatment routinely, symptoms such as coughing and nasal congestion significantly decreased, sleep quality improved, and daily activities became more stable. These findings indicate that ginger-honey preparation can serve as an effective, safe, and easily applied early intervention for ARI. The socialization activity proved effective not only in increasing community knowledge but also in demonstrating a direct positive impact on child health.